Experimental Validation for Hot Stamping Process by Using Taguchi Method - Mohd Fawzi, Zamri; Lim, Syh Kai; A. R., Yusoff (IOP Publishing, 2016)
Due to the demand for reduction in gas emissions, energy saving and producing safer vehicles has driven the development of Ultra High Strength Steel (UHSS) material. To strengthen UHSS material such as boron steel, it needed to undergo a process of hot stamping for heating at certain temperature and time. In this paper, Taguchi method is applied to determine the appropriate parameter of thickness, heating temperature and heating time to achieve optimum strength of boron steel. The experiment is conducted by using flat square shape of hot stamping tool with tensile dog bone as a blank product. Then, the value of tensile strength and hardness is measured as response. The results showed that the lower thickness, higher heating temperature and heating time give the higher strength and hardness for the final product. In conclusion, boron steel blank are able to achieve up to 1200 MPa tensile strength and 650 HV of hardness.